Treatment of pediatric lymphoma in Japan: Current status and plans for the future. Issue 4 (August 2015) - Kobayashi, Ryoji; Sunami, Shosuke; Mitsui, Tetsuo; Nakazawa, Atsuko; Koga, Yuhki; Mori, Takeshi; Tanaka, Fumiko; Ueyama, Jun‐ichi; Osumi, Tomoo; Fukano, Reiji; Ohki, Kentaro; Sekimizu, Masahiro; et al.
Abstract Results of pediatric lymphoma treatment have improved markedly over the past 30 years. In Hodgkin's lymphoma, the 5 year event‐free survival (EFS) was 81.5% in a retrospective study. In the ALB‐NHL03 study, the 5 year EFS according to clinical stage in patients with lymphoblastic T‐cell lymphoma (T‐LBL) was 70.6% for stage III and 88.9% for stage IV. In mature B‐cell lymphoma, the B‐NHL03 study indicated that the 4 year EFS according to treatment group was 94% for group 1, 98% for group 2, 84% for group 3, and 78% for group 4. Moreover, the 2 year EFS rate was 81% in Japanese advanced stage patients based on the international ALCL99 study. Thus, EFS >80% was achieved in any subtype of pediatric lymphoma. With regard to refractory or recurrent lymphoma, however, treatment methods for improvement of the survival rate in these patients still need to be developed. Also the difference between child, and adolescent and young adult patients still needs to be clarified, and treatment protocols developed. Although lymphoma treatment does not greatly change according to country, it does differ between other countries and Japan for some subtypes of lymphoma. In particular, the results of treatment of stage III T‐LBL in Japan are worse than those in the USA and Europe. The priority in future studies will be to collect data on these differences, and the reasons for these differences.